2014
DOI: 10.3329/fmcj.v8i2.20371
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Drug Abuse among Patients in Some Selected Addiction Rehabilitation Centers in Dhaka City

Abstract: :This study was done to find the pattern of drug abuse and its associated factors among the patients admitted in addiction rehabilitation centers. This descriptive cross sectional study was conducted among 150 drug addicted patients at the central drug addiction cure center at Tejgaon, Dhaka. Data were collected with a pre tested structured questionnaire. The study was conducted under the department of community medicine, National Institute of Preventive and Social Medicine (NIPSOM), Mohakhali, Dhaka during Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
5
4
1
Order By: Relevance
“…Over 60 per cent of CGs reported to be from lower SES (Table 1). This finding is consistent with previous studies (16) .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Over 60 per cent of CGs reported to be from lower SES (Table 1). This finding is consistent with previous studies (16) .…”
Section: Resultssupporting
confidence: 94%
“…Although evidences are growing in the western context, similar study is almost absent in Bangladesh. A few descriptive studies reported prevalence and sociodemographic nature of SU among University students (14) and recovering patients 15,16) but none of them considered HRQoL of SUs. Such effort in Bangladesh will facilitate intervention by indicating changes in physical, mental and social well-being of various treatment programs.…”
Section: Introductionmentioning
confidence: 99%
“…14 We also found that the peer pressure, pleasure and curiosity were the major influencing factor of abusing drug. This result is consistent with another study conducted by Riya et al 15 found that peer pressure was a major contributing factor (55.5%) for drug initiation. Similar findings were also reported by Gopiram,14 where peer influence, curiosity and sense of growing being were the major reasons of taking drugs among adolescents and young adults in India.…”
Section: Discussionsupporting
confidence: 83%
“…This trend of age does not differ much from the result of two previous studies done in our country 21,22 . Almost half of the respondents were in married group (47.7%), 7.3% were separate d or divorced.…”
Section: Sociodemographic Variablecontrasting
confidence: 30%